Neuronal development is promoted by weakened intrinsic antioxidant defences due to epigenetic repression of Nrf2 - Bell, Karen F.S.; Al-Mubarak, Bashayer; Martel, Marc-André; McKay, Sean; Wheelan, Nicola; Hasel, Philip; Márkus, Nóra M.; Baxter, Paul; Deighton, Ruth F.; Serio, Andrea; Bilican, Bilada; Chowdhry, Sudhir; et al. (Nature communications, 2015)
Forebrain neurons have weak intrinsic antioxidant defences compared with astrocytes, but the molecular basis and purpose of this is poorly understood. We show that early in mouse cortical neuronal development in vitro and in vivo , expression of the master-regulator of antioxidant genes, transcription factor NF-E2-related-factor-2 (Nrf2), is repressed by epigenetic inactivation of its promoter. Consequently, in contrast to astrocytes or young neurons, maturing neurons possess negligible Nrf2-dependent antioxidant defences, and exhibit no transcriptional responses to Nrf2 activators, or to ablation of Nrf2’s inhibitor Keap1. Neuronal Nrf2 inactivation seems to be required for proper development: in maturing neurons, ectopic Nrf2 expression inhibits neurite outgrowth and aborization, and electrophysiological maturation, including synaptogenesis. These defects arise because Nrf2 activity buffers neuronal redox status, inhibiting maturation processes dependent on redox-sensitive JNK and Wnt pathways. Thus, developmental epigenetic Nrf2 repression weakens neuronal antioxidant defences but is necessary to create an environment that supports neuronal development. Neurons in the brain are more susceptible to oxidative stress than astroglial cells but the molecular basis and biological reasons for this are poorly understood. Here the authors show that developing cortical neurons have reduced levels of the antioxidant transcription factor Nrf2 due to epigenetic silencing and that this is necessary for proper neuronal development.